ChemInform Abstract: The Molten Hydrated Flux Synthesis of a Novel Open‐Framework Copper Borophosphate and Its Structural Relation with the Precursors. Issue 41 (7th October 2014) - Zhao, Long; Liu, Wei; Ma, Xiaohong; Cao, Lixin; Su, Ge; Lu, Zhisheng
Abstract The new compound Cu2(H2O)[BP2O7(OH)] is synthesized by the molten hydrated flux method from a mixture of Cu(NO3)2·3H2O, NH4H2PO4, and H3BO3 in the molar ratio 1:1:10 (autoclave, 443 K, 5 d).